The complementary roles of men and women in human character evolution - Javier, Zainab (2009)
Men and women are equal but they are not identical. Consequently, they do not have identical rights and roles. Their differences, which subsequently made them complementary to each other, do not in any way suggest the superiority or inferiority of the other, not do they imply that they are competitors from opposing sides set to out maneuver each other. In fact, the variation in their makeup strengthens the ensuing partnership, transforming this into a vital alliance responsible for creating an environment conducive for a human being to e,bark to a noblest of endeavors- the endeavor to conquer his self.

The evolution of the human character which culminates in the domination of man over his self is the focal point of man's existence on this planet. Success in this life is not measured but by the success one has in taming his baser instincts and setting free the divine spark breathed into him by the divine source who made space and time.

How exactly do men's and women's roles fit into the scheme of things? How do the genders' roles affect human character development? Considering the roles it has delegated for men and women, is Islam not exit?

This paper is a humbly effort to shed light on the roles men and women play from the Islamic perspective, and their correlation with human character evolution. A world of mercy discusses the complex design of the cosmos aimed to provide ease for man. The perfection of man points to the destiny of the human being to reach the apex of perfection, attesting to his superiority over all of creation. Rights of women and roles of men and women in Islam is a presentation of the rights and roles of the genders from the Islamic point of view. The conclusion reiterates the roles men and women play and how these fit to the scheme of things, and to emphasize that Islam, 1,439 years ago and even long before the inception of the women's liberation movement in the west, has liberated women and placed them high on a pedestal and is, in fact, never discriminatory to women.
Keywords: Equality -- Religious aspects -- Islam